2010
DOI: 10.1128/jvi.02169-09
|View full text |Cite
|
Sign up to set email alerts
|

B Cells and Platelets Harbor Prion Infectivity in the Blood of Deer Infected with Chronic Wasting Disease

Abstract: Substantial evidence for prion transmission via blood transfusion exists for many transmissible spongiform encephalopathy (TSE) diseases. Determining which cell phenotype(s) is responsible for trafficking infectivity has important implications for our understanding of the dissemination of prions, as well as their detection and elimination from blood products. We used bioassay studies of native white-tailed deer and transgenic cer- Chronic wasting disease (CWD) is an infectious proteinmisfolding disease, or tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 76 publications
8
79
1
1
Order By: Relevance
“…Several studies have demonstrated that prions are present in the blood of sheep infected with scrapie and BSE, 16,17 deer incubating CWD, 18,19 and within the blood of patients with preclinical vCJD. 20 Where prion disease does result in widespread tissue distribution of infectious agent, it is likely that mucosal tissues, skin and secretory organs will contain prion.…”
Section: Excretion Of Prions Within Fecesmentioning
confidence: 99%
“…Several studies have demonstrated that prions are present in the blood of sheep infected with scrapie and BSE, 16,17 deer incubating CWD, 18,19 and within the blood of patients with preclinical vCJD. 20 Where prion disease does result in widespread tissue distribution of infectious agent, it is likely that mucosal tissues, skin and secretory organs will contain prion.…”
Section: Excretion Of Prions Within Fecesmentioning
confidence: 99%
“…Blood plasma from prion-infected hosts is notorious for its poor transmission in conventional prion infectivity bioassays using sentient experimental animals [19,21] and does not act as a seed for the initiation of in vitro PMCA [40]. Furthermore, plasma from scrapie-affected sheep was less efficient than either whole blood or white blood cells in transmission of the disease when recipient scrapie-free sheep were inoculated with these samples by the intravenous route [19].…”
Section: Discussionmentioning
confidence: 99%
“…Our studies here support the view that the level of prion infectivity in blood from prion-diseased individuals may be underestimated when assessed by intracerebral inoculation of rodents in comparison with bioassay of similar material in other experimental systems. This is particularly pertinent to our assessment here of prion-infected plasma that could be diluted by several orders of magnitude and still trigger a phenotypic response in the PrP transgenic Drosophila, but appears to contain a low level of infectivity when assayed in other systems [10,[15][16][17][18][19][20][21]. One possibility for the efficient detection of scrapie-infected sheep plasma by PrP transgenic Drosophila is that this invertebrate host does not normally express PrP and may therefore not have evolved suitable defence mechanisms that efficiently remove or sequester misfolded neurotoxic forms of this protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations